Molecular analysis of Staphylococcus aureus isolated from clinical samples and natural flora: Molecular analysis of S. aureus isolated from clinical samples - Abdulbaqi, Amal; Ibrahim, Ashraf Sobh (Cellular and Molecular Biology, 2023)
A total of 100 samples collected from the wound, abscess skin, and normal human flora were investigated for S. aureus identification. Overall, in 40 samples, S. aureus isolates were present, out of which most strains were isolated from normal human flora (50.0%), followed by wound (37.5%) and burn (12.5%) samples. Moreover, S. aureus isolates from all samples could produce extracellular enzymes (catalase, coagulase, urease, and hemolysin–ß) as virulence factors except for some isolates from normal flora samples (unable to produce coagulase enzymes). Therefore, genes encoding the enzymes coagulase and hemolysin were evaluated in 20 S. aureus isolates by PCR-specialized primers targeting co-specific genes. The PCR analysis revealed that clinical isolates included both genes. Contrarily, 6 isolates of the normal flora lacked the coa gene, revealing bacterial fingerprints that can be used to distinguish between isolated bacteria and human beings.